CONSUMERS’ PREFERENCE AND SATISFACTION OF GSM SERVICE PROVIDERS AMONG STUDENTS OF TERTIARY INSTITUTIONS IN LAGOS STATE, NIGERIA (Nigerian Journal of Technology, 2018)
This study contributes to intellectual discuss on consumer preference and satisfaction for GSM service providers in the context of students of tertiary institution in Lagos State, Nigeria. Using primary data, the study provide answer to four research questions and tested four hypotheses with a view to establish the influence of consumers’ preference and satisfaction of GSM service providers in Nigeria. The findings revealed a significant positive relationship between service assurance, service empathy, service reliability, service responsiveness and customers’ satisfaction of GSM service provision among students of tertiary institution in Lagos State. Also, the study also indicated that all variables accounted for 64% of the variance in service satisfaction (R2 = .645; F = 20.400, P = .000). Nonetheless, service reliability (? = .267, t = 3.439, p = .001) was found to have the greatest influence on service satisfaction followed by service assurance (? = .170, t = 2.987, p = .005) and service responsiveness (? = .135, t = 2.056, p = .046). On the other hand, only service empathy was not found to have influence service satisfaction.  http://dx.doi.org/10.4314/njt.v37i4.33